The effect of ultrasonic processing on physical and chemical properties of milk‐based soft, brine cheese - Ammar Kadi; Uday Bagale; Irina Potoroko (Indonesian Journal of Biotechnology, 2022)
Many earlier studies have documented pasteurization problems in the dairy industry. As a result, ultrasonic processing has been researched as a non‐heat alternative to pasteurization. In this study, milk‐based soft cheese was treated using various sonication times (0, 1, and 3 min) at a set frequency (22 kHz) with an amplitude of 60% of 630 W and different ripening periods (0, 15, 30, and 60 days) in brine (15%), stored at 4 °C, to reduce heat treatment and increase yield. The physicochemical parameters of white cheeses were examined over next 60 days and compared with a control cheese. The result showed that ultrasound had no significant effect on the cheeses in terms of their fat and protein content on storage. Compared to the control sample, ultrasound treatment improved the taste and aroma ratings due to increased lipolysis and proteolysis. In terms of overall acceptability, the ultra‐filtrate cheese sonicated for 3 min received the highest marks compared to the control. Sonication for 3 min treated fresh milk showed the maximum yield (190.5 g/L milk) compared to untreated raw milk yields (150.32 g/L).